Precise correction of a spectrum of β-thalassemia mutations in coding and non-coding regions by base editors - Kirti Prasad; Nivedhitha Devaraju; Anila George; Nithin Sam Ravi; Joshua Paul; Gokulnath Mahalingam; Vignesh Rajendiran; Lokesh Panigrahi; Vigneshwaran Venkatesan; Kartik Lakhotiya; Yogapriya Periyasami; Aswin Anand Pai; et al. (Elsevier, 2024)
β-thalassemia/HbE results from mutations in the β-globin locus that impede the production of functional adult hemoglobin. Base editors (BEs) could facilitate the correction of the point mutations with minimal or no indel creation, but its efficiency and bystander editing for the correction of β-thalassemia mutations in coding and non-coding regions remains unexplored. Here, we screened BE variants in HUDEP-2 cells for their ability to correct a spectrum of β-thalassemia mutations that were integrated into the genome as fragments of HBB. The identified targets were introduced into their endogenous genomic location using BEs and Cas9/homology-directed repair (HDR) to create cellular models with β-thalassemia/HbE. These β-thalassemia/HbE models were then used to assess the efficiency of correction in the native locus and functional β-globin restoration. Most bystander edits produced near target sites did not interfere with adult hemoglobin expression and are not predicted to be pathogenic. Further, the effectiveness of BE was validated for the correction of the pathogenic HbE variant in severe β0/βE-thalassaemia patient cells. Overall, our study establishes a novel platform to screen and select optimal BE tools for therapeutic genome editing by demonstrating the precise, efficient, and scarless correction of pathogenic point mutations spanning multiple regions of HBB including the promoter, intron, and exons.